2007
DOI: 10.1093/molbev/msm228
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Diversification of Msx Protein in Metazoan Evolution

Abstract: Msx (/msh) family genes encode homeodomain (HD) proteins that control ontogeny in many animal species. We compared the structures of Msx genes from a wide range of Metazoa (Porifera, Cnidaria, Nematoda, Arthropoda, Tardigrada, Platyhelminthes, Mollusca, Brachiopoda, Annelida, Echiura, Echinodermata, Hemichordata, and Chordata) to gain an understanding of the role of these genes in phylogeny. Exon-intron boundary analysis suggested that the position of the intron located N-terminally to the HDs was widely conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…Later on, Msx1 and Msx2 expression domains become progressively restricted to the RP, whereas Msx3 expression persists in the dorsal part of the spinal cord excluding the RP (Hill et al, 1989;Robert et al, 1989;Shimeld et al, 1996). HD sequences and Engrailed homology 1 motif (Eh1) domains in their N-terminus are highly conserved between Msx1, Msx2 and Msx3 and between species (Takahashi et al, 2008). Consistent with the presence of an Eh1 repressor domain, Msx1 and Msx2 are described as transcriptional repressors.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Later on, Msx1 and Msx2 expression domains become progressively restricted to the RP, whereas Msx3 expression persists in the dorsal part of the spinal cord excluding the RP (Hill et al, 1989;Robert et al, 1989;Shimeld et al, 1996). HD sequences and Engrailed homology 1 motif (Eh1) domains in their N-terminus are highly conserved between Msx1, Msx2 and Msx3 and between species (Takahashi et al, 2008). Consistent with the presence of an Eh1 repressor domain, Msx1 and Msx2 are described as transcriptional repressors.…”
Section: Introductionmentioning
confidence: 93%
“…Since amino acids F and S of the Msx Eh1 motif are required for its interaction with Groucho/TLE family members (Takahashi et al, 2008;Rave-Harel et al, 2005;Goldstein et al, 2005), they were replaced by G and A in Msx1 (Msx1*) and Msx2 (Msx2*) to abolish their repressive activity (Fig. 5Dc).…”
Section: Loss Of Msx1 and Msx2 Functions Alters Interneuronal Differementioning
confidence: 99%
See 1 more Smart Citation
“…The Emx sequence was deposited in the DDBJ database with accession number AB439506. Tubifex Zic (Ttu-Zic, AB231870) and Tubifex Msx (Ttu-Msx, AB302957) cDNAs were previously described (Aruga et al 2006;Takahashi et al 2008). …”
Section: Pcr Cloning and Rt-pcr Analysismentioning
confidence: 99%
“…To learn whether the aforementioned spatiotemporal expression pattern of Ttu-Zic is widespread among genes expressed in the mesodermal cell lineage (i.e., in the germ band), we examined the expression pattern of another developmental tool-kit gene, Ttu-Msx (Takahashi et al 2008), which was shown to be expressed in the mesodermal lineage in a preliminary observation. Expression of Ttu-Msx begins at late stage 14, and hybridization signals are detected as transverse, regularly repeating stripes in the anterior region of the mesodermal germ band (Fig.…”
Section: Expression Of Ttu-zic During Embryo Body Elongation (Stages mentioning
confidence: 99%